Expectativas de la familia indígena frente a la educación. Análisis de caso en la Comunidad Cuniburo, parroquia Cangahua - Rea Oviedo, Martha Paola (2018)
It is of vital importance for the indigenous families in the community of Cuniburo to improve the quality of life of their children, taking into account that education currently guarantees social change, for this reason the families of the community look for the best options in the field of education for their children either: in the surrounding communities or in the particular educational or fiscal units of the city of Cayambe. The comuneros, before the future Millenium Education Unit, aspire that fiscal education change substantially for their children, that they provide a quality education, warmth and cultural relevance, and change the paradigm and the devaluarían of education in the communities This research is carried out under the qualitative method, the collection of information is through the interview, and the search of information in books, to support the processes and historical facts about education in Ecuador.